2015
DOI: 10.1111/dmcn.12752
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of body composition in children with cerebral palsy: a cross‐sectional study inNorway

Abstract: Aim The assessment of growth and body composition is challenging in children with cerebral palsy (CP). The aim of this study was to compare clinical assessments of body composition with measurements obtained using dual‐energy X‐ray absorptiometry (DXA) in this population. Method Knee height, weight, and triceps and subscapular skinfold thickness (SFT) were measured in 47 children with CP (age range 8–18y; 18 females, 29 males). Height was estimated from knee height, and used to calculate body mass index (BMI).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
60
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 36 publications
13
60
0
3
Order By: Relevance
“…These results were comparable to the results of Oeffinger et al and Finbr aten et al 13,33 As reported by other authors, the mean body fat percentage in children in GMFCS levels III to V in this study was significantly higher than in children in GMFCS levels I and II. These results were comparable to the results of Oeffinger et al and Finbr aten et al 13,33 As reported by other authors, the mean body fat percentage in children in GMFCS levels III to V in this study was significantly higher than in children in GMFCS levels I and II.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results were comparable to the results of Oeffinger et al and Finbr aten et al 13,33 As reported by other authors, the mean body fat percentage in children in GMFCS levels III to V in this study was significantly higher than in children in GMFCS levels I and II. These results were comparable to the results of Oeffinger et al and Finbr aten et al 13,33 As reported by other authors, the mean body fat percentage in children in GMFCS levels III to V in this study was significantly higher than in children in GMFCS levels I and II.…”
Section: Discussionsupporting
confidence: 92%
“…33,35 Children in GMFCS levels I and II were more likely to have low body fat percentage than children in GMFCS levels III to V (14.3% vs 1.79%, Table III). 33,35 Therefore, with the same fat mass, a child with lower lean body mass would have a higher body fat percentage. Another explanation could be a methodological bias: in concordance with other studies, children in GMFCS levels III to V in this study had less lean body mass by DXA (which is a surrogate for muscle mass and a main component of body weight) than children in GMFCS levels I and II (Table II).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbidities in the medically complex population also impact body composition. Among children with cerebral palsy, those with greater functional impairment (Gross Motor Function Classification System Level III or IV) have higher fat percentages and lower lean body mass than children with less functional impairment (Gross Motor Function Classification System Level I or II) [11]. …”
mentioning
confidence: 99%
“…Due to substantial deficits in overall lean tissue , 7-10 normal BMIs in CP may disguise excess adiposity in visceral or other ectopic adipose depots (e.g., liver, muscle, bone marrow, etc.). 11 There is some evidence to suggest greater general adiposity in children with CP; 12 however, this has yet to be well-studied in the adult CP population.…”
mentioning
confidence: 99%